2021
DOI: 10.3390/ijerph182211790
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic Status and Orthodontic Treatment Need of 12- and 15-Year-Old Greek Adolescents: A National Pathfinder Survey

Abstract: The purpose of this research was to assess the orthodontic status and orthodontic treatment needs of 12- and 15-year-old schoolchildren in Greece, in relation to sociodemographic factors and parental education level. A total of 1102 12-year-old children and 1131 15-year-old adolescents across Greece were assessed using the Modified Dental Health component (DHC) of the Index of Orthodontic Treatment Need (IOTN). An amount of 38.7% of 12-year-olds and 33.7% of 15-year-olds were in definite need of orthodontic tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
3
4
0
Order By: Relevance
“…The difference in prevalence of sagittal malocclusions between neighboring countries may be attributed to ethnic differences and sample composition. Crowding, deep bite, and posterior crossbite were dominant malocclusion traits found in the present study, which is in accordance with the findings in the Greek survey [62]. Crowding was the most frequently reported malocclusion in Serbian children, as well as globally [61].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The difference in prevalence of sagittal malocclusions between neighboring countries may be attributed to ethnic differences and sample composition. Crowding, deep bite, and posterior crossbite were dominant malocclusion traits found in the present study, which is in accordance with the findings in the Greek survey [62]. Crowding was the most frequently reported malocclusion in Serbian children, as well as globally [61].…”
Section: Discussionsupporting
confidence: 91%
“…Findings of the previous epidemiological study in Serbia [5] also indicated high percentage of children with neutrocclusion (60.3% and 58.5% of 12-year-old and 15-year-old children, respectively). Similar results were presented in a national pathfinder survey in Greece [62]. Authors reported an Angle Class I molar relationship in 49.4% and 52.3% of 12-year-old and 15-year-old children, respectively.…”
Section: Discussionsupporting
confidence: 83%
“…[ 27 ] Differences may be due to age of study populations as malocclusion has been shown to worsen with age,[ 28 ] as well as ethnic variations in perceptions of beauty. Male participants were found to have a greater need for treatment than females as has been seen in studies in Greece[ 29 ] and Nigeria,[ 14 ] whereas a Syrian study did not find any sex predilection. [ 30 ]…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, it was disturbing to note that children with early loss of primary molars presented no evidence of any space maintenance. This might be attributed to socioeconomic status and lack of awareness of the importance of space maintenance 25 . However, socioeconomic status was not assessed in the present study as a major proportion of the population utilize publicly funded healthcare services.…”
Section: Discussionmentioning
confidence: 99%